PENGEMBANGAN PEMBELAJARAN GEOGRAFI MELALUI MEDIA KARTU UNO - Desy Mauliya; M.Thoha B.S Jaya; Darsono Darsono (Faculty of Teacher Training and Education, University of Lampung, 2015)
This research aimed to produce a product in the from of card media that can increase the activity and student learning outcomes, and analyze the effectiveness of using card media in Geography teaching in high school. This research approach was the approach of Research and Development by using a development design of Dick and Carey. The final product of this research is learning development through the medium of Uno cards that have been evaluated by experts materials, instructional media experts, as well as a limited test. This research and development to produce media Uno card was developed based on the results of the analysis of the needs of students, as a medium of learning that can improve student learning out comes and can be used in teaching Geography in senior higt school, and media card Uno effective in improving student achievement seen from the improvement of student learning outcomes or an increased number of students who complete the KKM.Penelitian ini bertujuan menghasilkan suatu produk berupa media kartu yang dapat meningkatkan motivasi dan hasil belajar siswa, serta menganalisis efektifitas penggunaan media kartu pada pembelajaran Geografi di SMA. Pendekatan penelitian ini adalah pendekatan Research and Development dengan menggunakan desain pengembangan Dick and Carey. Produk akhir penelitian ini berupa media pembelajaran yang telah dievaluasi oleh ahli materi, ahli desain model pembelajaran, serta uji terbatas. Penelitian pengembangan ini menghasilkan (1) media kartu UNO dikembangkan berdasarkan hasil analisis kebutuhan (need assessement) siswa, sebagai media pembelajaran yang dapat meningkatkan hasil belajar siswa dan dapat digunakan pada pembelajaran Geografi di SMA, dan (2) media kartu UNO efektif dalam meningkatkan prestasi belajar siswa dilihat dari peningkatan hasil belajar siswa atau peningkatan jumlah siswa yang tuntas KKM.Kata kunci: aktivitas belajar, hasil belajar geografi, media kartu uno